(untitled) (Legal journal - Research in Legal and Social Sciences, 2021)
This brief essay presents an overall pic ture of political funding, making questions on its importance and confronting it with the reality. Also, it explores in general the most relevant legal norms that regulate that matter in the Republic of Paraguay. Furthermore, this essay also covers the main acts and their amendments, with simple explanations of the different types of financings that currently exist, and a small introduction on the current discussion on illegal financing of political parties. The study also covers the international reality b y analyzing the prominent case called Lava Jato. It also includes important definitions in order to better comprehend this topic, which will allow the reader of this essay to count with basic tools to discuss on the most outstanding points around political funding. Even though it is a summary, it includes comments on case studies regarding the illegal financing of political parties that came to light within the scheme of corruption of the mentioned case. This essay finishes with a comment on the need to pro pose a criminal act that classifies the illegal financing of political parties.